2017
DOI: 10.1007/s11926-017-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Syndrome and the Rheumatologist

Abstract: The most commonly reported drugs are allopurinol, sulfasalazine and minocycline, which pose a very high risk for DRESS syndrome development, followed by strontium ranelate and dapsone. Other, less commonly reported, drugs include leflunomide, hydroxychloroquine, non-steroidal anti-inflammatory drugs, febuxostat, bosentan and solcitinib. Reaction to some drugs is strongly associated with certain HLA alleles, which may be used to screen patients at risk of serious toxicity. DRESS syndrome is a serious reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 80 publications
0
8
0
4
Order By: Relevance
“…Eosinophilia within clozapine-related DRESS also merits some attention. Eosinophilia in DRESS related to other drugs varies largely (Adwan, 2017;Behera et al, 2018;Cacoub et al, 2011;Ghannam et al, 2017;Kardaun et al, 2013). In our sample, it was observed in around 60% of the patients.…”
Section: Discussionmentioning
confidence: 53%
“…Eosinophilia within clozapine-related DRESS also merits some attention. Eosinophilia in DRESS related to other drugs varies largely (Adwan, 2017;Behera et al, 2018;Cacoub et al, 2011;Ghannam et al, 2017;Kardaun et al, 2013). In our sample, it was observed in around 60% of the patients.…”
Section: Discussionmentioning
confidence: 53%
“…Aunque su etiopatogenia aún es desconocida, se han involucrado factores de predisposición genética, reactivación de infecciones virales 9,10 (principalmente virus herpes humano [VHH] 6 y 7, Epstein Barr y citomegalovirus [CMV]) y alteraciones en el metabolismo de fármacos, como acetilación lenta y defectos en la detoxificación que resultan en metabolitos reactivos capaces de desencadenar una respuesta inmune alterada 2 . Entre los fármacos clásicamente asociados a este síndrome se describen anticonvulsivantes (35%), alopurinol (18%), sulfas (12%) y antibióticos (11%) 8 (Tabla 1), aunque en estudios más recientes, los antibióticos ocupan el primer lugar (74%) 7 y, en una serie de pacientes reumatológicos, la sulfasalazina ocupó el segundo lugar luego del alopurinol 11 .…”
Section: Discussionunclassified
“…Typical DRESS patients would have been exposed to a high-risk medication [ 7 ]. A retrospective analysis of 45 patients with DRESS showed that the most common causative drug group was antibiotics (28.9%), followed by anticonvulsants (26.7%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%